P20 Potential impact of updated UK guidelines for use of post exposure prophylaxis following sexual exposure in a London sexual health service. (23rd May 2012) - Snell, L; Edwards, S G; Benn, P D
Abstract : Background: Updated UK guidelines for post exposure prophylaxis following sexual exposure (PEPSE) outline new thresholds for when PEPSE is recommended (R), considered (C) or not recommended (NR). Aim/Objective: We compared practice and outcomes according to 2006 and 2011 guidelines. Methods: Retrospective review of electronic patient records between 20 January 2011 and 7 November 2011. Information regarding presentation, recommendations and outcomes were collected. Risk estimates were compared with guidelines. Blood abnormalities were classified grades I-IV. Data were analysed using Microsoft Excel. Results: Of 325 requests to a London sexual health service, PEPSE was issued on 281 occasions to 268 patients. Gender: male n=258, female n=10, median age: 32 years, sexual orientation: men who have sex with men n=236, heterosexual n=25, not recorded n=7. Risk exposure: unprotected anal (n=263) and vaginal (n=26) intercourse. Source details: HIV+ n=112 (40%), on antiretroviral therapy n=31, viral load known 40 (14%) (<50 n=26, >50 n=14). 71 (26%) reported taking PEPSE ≥ once (range 1–5) previously. 99% commenced PEPSE within 72 h (median 30). Comparing those classified as R (n=258) and C (n=21) according to 2006 guidelines, 27 (10%) were reclassified NR using 2011 guidelines. Completion of 28 days PEPSE was reported in 59% cases, 100% adherence in 87%. Eight stopped early due to side effects (n=4) or the source tested HIV- (n=4). 148/268 (55%) had ≥1 blood abnormality, grade I-II (n=196) and grade III-IV (n=29). 1 patient developed acute interstitial nephritis. 196/268 (73%) underwent ≥1 screen for sexually transmitted infections; chlamydia (n=27), gonorrhoea (n=17), syphilis (n=4) and hepatitis B (n=1). Of 243 due 4-month follow-up, 52% have tested HIV− (n=122) and HIV+ (n=4). Conclusions: We report high rates of repeat PEPSE, side effects/blood abnormalities and poor completion rates. Updated guidelines may result in a modest reduction in the use of PEPSE.